Intervención arquitectónica del edificio de la Cruz Roja de Tungurahua - Christian Sebastián Pazmiño Martínez (2024)
The architectural heritage of the modern movement is a relevant topic for Ambato's culture due to the need for its study and dissemination. The architectural intervention in Tungurahua's Red Cross building seeks to improve the conditions of a modern movement construction in Ambato, highlighting the importance of preserving its architectural and symbolic identity, justified by its relevance as architectural heritage and its meaning for the community. The research and proposal focus on how the building can be intervened, considering the current institutional needs and the identified problems, which include a loss of the architectural values of the building, as well as functional conflicts of spaces that do not fully adapt to the needs of their current functions. The project's objectives focus on a diagnosis of the current state, the identification of internal needs, and the proposal of solutions that integrate the building's history with contemporary demands. The methodology includes a descriptive analysis of the current context and the synthesis of relevant results to obtain general criteria for intervention, such as the optimization of internal spaces, as well as a formal intervention that highlights the institutional image through its formality and aesthetics on the facade. Subsequently, the conceptualization and development of an architectural approach in accordance with the identified needs and proposed criteria are developed. Finally, through digital representation tools, an intervention proposal is presented in accordance with the previous research